Stališča pripadnikov Slovenske vojske do mednarodnega terorizma - Čaleta, Denis (Teorija in praksa, 2009)
This scientific contribution lies in addressing the role of the armed forces in the field of tackling terrorism and, in particular, the views of its members on international terrorism. In this framework we examine the important scientific dilemma of whether there is a divergence in threat perceptions of international terrorism between basic public opinion and the opinions of service members, police officers, members of the intelligence and other bodies regarding terrorist threats. In the event of a divergence this could hypothetically mean a discrepancy between real terrorist threats to security on one hand as perceived by armed forces members especially on international operations and missions and, on the other hand, the awareness of such threats in the wider social community. An analysis is made of the results of a survey carried out with a qualified target group of Slovenian Armed Forces members which examined the factors encouraging international terrorist activities. With regard to the identification of international terrorist threats, I empirically noted a gap between the normative and the actual, as well as between the normative and identified features. This could pose a big problem if it also implies a gap between the positions of members of counter-terrorist structures and the policies of their organisations.
Keywords: Armed forces; Oborožene sile; Slovenian Armed Forces; Slovenian Army; Slovenska vojska; International terrorism; Mednarodni terorizem; terorizem; boj proti terorizmu; analize